Effects of chestnut hydrolysable tannin enrichment in the artificial diet of forager bees, Apis mellifera - Sagona, S.; Minieri, S.; Coppola, F.; Gatta, D.; Casini, L.; Palego, L.; Felicioli, A.
Hydrolysable tannins are polyphenolic molecules contained in plant foodstuffs, potentially toxic for animals. Since tannins have been found in some bee products such as bee pollen, propolis, and honey, this work aimed to test the effects of tannins dietary assumption on bees' health. Results showed that supplementation of honey bees diets with 0.05 percent (w/w), as naturally amount reported in the honey, and 0.5 percent (w/w)of tannins significantly reduced bees' survival in a dose-dependent manner. In honey bees fed with a 0.5 percent tannins-enrichment diet a significantly decreased phenoloxidase activity than those fed with a 0.05 percent tannins-enrichment diet and with only syrup was recorded. Conversely, glucose oxidase activity significantly increased in honey bees fed with 0.5 percent tannins-enrichment diet than those with a 0.05 percent tannins-enrichment diet and only syrup. No differences were detected in glutathione S-transferase activity between honey bees fed with tannins-enrichment diets and syrup. Therefore, a naturally amount of hydrolysable tannins in foods can weakly affect bee wellness, whereas high levels of tannins can have a negative impact on honey bees' immunity and metabolism leading to a reduction of lifespan
Keywords: HONEY BEE; HYDROLYSABLE TANNINS; PHENOLOXIDASE; GLUCOSE OXIDASE; GLUTATHIONE S-TRANSFERASE